Synthesis of Substituted Pyrido-oxazine through Tandem SN2 and SNAr Reaction - Pathan, Mosim Amin; Khan, Faiz Ahmed (SynOpen, 2018)
Pyrido-oxazine derivatives have been synthesized by employing tandem SN2 and SNAr reaction between 2,4,6-tribromo-3-(2-bromoethoxy)pyridine or 2,4,6-tribromo-3-(3-bromopropoxy)pyridine and a variety of primary amines. Moderate to good regioselectivity in favor of cyclization at the 2-position is observed. Pyrido-oxazine products thus generated are converted into biarylated pyrido-oxazine and terpyridine ligands.
Keywords: pyridine; terpyridine; pyrido-oxazines; Suzuki coupling; Stille coupling